Discourse Analysis and the Capacity of Linguistic Studies to Theorize a Framework - Yusuf Murtadha (Indonesian Journal of Arabic Studies, 2023)
Purpose: This paper focuses on developments, such as Text linguistic, Discourse analysis and Critical discourse analysis, that was introduced in the field of linguistics in the Nineteenth century. These are approaches that refer to language units (text, discourse, conversation and narratives) as social situation with multiple relations, and focus in their analysis on social details that is beyond structure, rather, a careful observation of nature and interpersonal relation. Design/ methods/approach: this paper adopts descriptive analytical method to describe various scientific phenomena that are related to the theoretical capacity of linguistic over other discipline, as well as details of different approaches, procedural similarities and Arabic studies’ adaptation to the development of linguistic in area of discourse analysis. Findings: This paper concluded that the linguistic revolution and transformation towards language units have made analysis focus on social and cognitive aspects, intellectual and intentional strategy, and ideological orientation, which has drawn other studies to the textual linguistic process of analysis.